TRADITIONAL KNOWLEDGE IN INDIA AND BIODIVERSITY CONSERVATION - Ahuja, Maansi (Trinity Law Review, 2026)
Traditional Knowledge (TK), developed over generations by indigenous communities, is vital for food security, local healthcare, and ecosystem preservation. However, modern socio-economic shifts and changing land ownership increasingly threaten its survival. Globally, frameworks like the Convention on Biological Diversity (CBD) and the Nagoya Protocol mandate prior informed consent and equitable benefit-sharing to safeguard these resources.India has actively codified these principles through a robust domestic legislative framework. Key mechanisms include the Biological Diversity Act (2002), which decentralizes ecological governance via People’s Biodiversity Registers, and the PPV&FR Act (2001), which secures farmers' rights. Additionally, legal mandates protect culturally significant "Sacred Groves," while state-backed projects like the Traditional Knowledge Digital Library (TKDL) directly combat biopiracy. This paper analyzes India's multi-tiered conservation strategies, concluding that while documentation is extensive, enhancing grassroots awareness and refining codified benefit-sharing schemes are critical to securing full community participation and long-term sustainability.
Keywords: Blockchain Technology; Financial Technology; FinTech; Financial Institution